Social production and consumption of space: study of public-market in Bandung, Indonesia - Ekomadyo, Agus; Triwardhani, Ike J. (Journal of Architecture and Urbanism, 2024)
This paper aims to examine the role of architecture in social production and consumption of space, using public markets –architectural artifacts with rich social contents– as cases. This research adopts Low’s (2017) concept of social production of space and Dovey’s (2010) social constructivism of place to uncover the social production and consumption of public markets’ space. Cihapit and Pamoyanan market in Bandung, Indonesia, are selected as research cases, due to their cultural contents, appealing to consumers from middle to upper class society. It is found several roles of architecture in social production and consumption of public market space: building typology and morphology signifies historical context of development; architectural buildings contributes to formalize trading activities and elevating social class of market traders; commodities zoning is organized based on functional and socio-historical consideration; spatial intensity is determined by access and commodities zoning; informal atmosphere emerges as a distinctive advantage of public markets; and spatial quality is relative depends on governance capacity. Although normative criteria for good design can be formulated, in practice, spatial quality of public market is relative and depends on its capacity for spatial governmentality. By exploring social production and consumption of space and place provides broader perspective on the social practices of architecture, emphasizing its contribution for social and humanity studies.